Philosophy of Unity of Science: Concept and Implications of Learning Practice at UIN Walisongo Semarang - Pratiwi, Dian; Nasikhin, Nasikhin; Fihris, Fihris (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Philosophy is understood as a discipline that investigates the nature of reality, addresses human experiences, and seeks to provide solutions to challenges across various fields. The philosophy of unity of science serves as a foundational concept, emphasizing the interrelatedness of all scientific disciplines. This research aims to explore and analyze the Philosophy of the Unity of Science as a conceptual foundation in the context of education at UIN Walisongo Semarang. The research method in this article is a literature study, with data collected through observation and documentation related to the Philosophy of Unity of Science course. The results of the study show that the application of the Paradigm of Unity of Science at UIN Walisongo has a positive impact on education, thus allowing students to develop a holistic understanding of the relationship between religion, science, and society. The implications of the Philosophy of Unity of Science in learning practice involve deep conceptual understanding, integration of cross-disciplinary knowledge, development of cross-disciplinary skills, and holistic thinking. This research makes a significant contribution to the understanding of the concept of the Philosophy of Unity of Science and its implications in the context of higher education, illustrating its relevance and potential to form a generation of adaptive and insightful leaders in the face of the complexities of the modern world. The conclusion of this study provides an in-depth understanding of how the Philosophy of Unity of Science can contribute to the development of the curriculum, learning approach, and character formation of students at UIN Walisongo Semarang.